Quantifying top-down control and ecological traits of the scyphozoan Aurelia aurita through a dynamic plankton model - Ramírez-Romero, Eduardo; Molinero, Juan Carlos; Paulsen, Matthias; Javidpour, Jamileh; Catriona, Clemmesen; Sommer, Ulrich (Oxford University Press, 2018)
Aurelia aurita (Linneaus, 1758) is a cosmopolitan scyphozoan, probably the most investigated jellyfish in temperate and highly productive coastal ecosystems. Despite a prominent top-down control in plankton food webs, a mechanistic understanding of A. aurita population dynamics and trophic interactions has been barely addressed. Here we develop a food web dynamic model to assess A. aurita role in the seasonal plankton dynamics of the Kiel Fjord, southwestern Baltic Sea. The model couples low trophic level dynamics, based on a classical Nutrient Phytoplankton Zooplankton Detritus (NPZD) model, to a stage-resolved copepod model (referencing Pseudocalanus sp.) and a jellyfish model (A. aurita ephyra and medusa) as consumers and predators, respectively. Simulations showed the relevance of high abundances of A. aurita, which appear related with warm winter temperatures, promoting a shift from a copepod-dominated food web to a ciliate and medusa dominated one. The model captured the intraspecific competition triggered by the medusae abundance and characterized by a negative relationship between population density and individual size/weight. Our results provide a mechanistic understanding of an emergent trait such as size shaping the food web functioning, driving predation rates and population dynamics of A. aurita, driving its sexual reproductive strategy at the end of the pelagic phase.
https://openpolicyfinder.jisc.ac.uk/id/publication/648
Keywords: Medusas - Distribución geográfica; Jellyfish; Stage-resolved model; Planktonic food web; Population modeling; Coastal ecosystem